Towards the Promotion of Fuel Briquettes Using Municipal Solid Waste and Residual Biomass in Burundi - Manirakiza, Norbert; Ndikumana, Théophile; Jung, C. Gisèle (International Journal of Environment, 2020)
The issue of domestic energy is still a major concern in developing countries. A sound knowledge of fuel characteristics is a major asset for their acceptability and their distribution. Samples of briquettes made partially with Municipal Solid Waste (MSW) were collected in several companies with unknown characterization. This study intended first to characterize them for physical and chemical properties. Subsequently, energy content of the briquettes and the energy price are presented and compared to those of charcoal and peat, which is typically used by the local population as fuel. To classify the different briquettes according to their quality in terms of rate as well as their level in fire resistance, cooking tests and heating curves have been made. The calorific value of the studied briquettes varied from 12.3 to 18.6 MJ/kg compared to 32.5 MJ/kg for charcoal and 14.7 MJ/kg for peat. Consequently, their value as viable substitutes for charcoal or peat is apparent. However, some samples burn very quickly and do not provide prolonged heating while other samples have a slow rate of combustion and release little energy. Finally, the briquettes using MSW have a low price between $0.16 and $0.19/kg compared to the price of $0.53/kg for charcoal and $0.20/kg for peat. The promotion of these briquettes as a valuable substitution fuel is proved and contribute to sustainable development by reusing MSW and avoiding deforestation.